Global burden and trends of norovirus-associated diseases from 1990 to 2021 an observational trend study - Zhu, MengLan; Huang, ZiLing; Liu, TongTong; Wu, ChenNan; Shang, ZhiHan; Zhang, LuLu (Frontiers in Public Health, 2025)
BackgroundNorovirus remains a significant viral cause of waterborne and foodborne gastroenteritis outbreaks and epidemics worldwide. The burden of norovirus extends across different income settings.MethodsLeveraging secondary data from the 2021 Global Burden of Diseases Study, our analysis spanned the period from 1990 to 2021 to assess the burden of norovirus-associated diseases (NADs). We utilized descriptive statistics to examine global mortality rates and disability-adjusted life years (DALYs). For trend analysis, we employed annual percentage change (EAPC) through linear regression and applied Joinpoint analysis to identify significant changes over time. A comprehensive age-period-cohort model evaluated the key mortality risk factors. Furthermore, a Bayesian age-period-cohort analysis was conducted to forecast trends up to 2035, providing valuable insights for policy formulation and resource allocation.ResultsIn 2021, the global age-standardized mortality rate (ASMR) for NADs was 1.62 per 100,000 population (95% UI: 0.35 to 2.91), while the age-standardized DALY rates (ASDR) was 79.02 years per 100,000 population (95% UI: 26.61 to 132.26). A downward trend was observed in most regions and countries, with EAPC of −4.29% (95% UI: −4.53 to −4.05) for ASMR and −4.40% (95% UI: −4.62 to −4.19) for ASDR from 1990 to 2021. Notably, children under 5 years old had considerably higher ASDR: 475.52 years (95% UI: 160.73 to 893.72) per 100,000 for males and 335.44 years (95% UI: 112.29 to 623.48) per 100,000 for females. Mortality risk from NADs escalated with age, with a peak of 69.27 (95% CI: 64.04 to 74.92) per 100,000 for the under-five age group, and 11.38 (95% CI: 10.59 to 12.22) per 100,000 for individuals over 95 years. Bayesian Age-Period Cohort projections indicate a continued decline in ASMR and ASDR through 2035.DiscussionBetween 1990 and 2021, ASMR and ASDR for NADs significantly declined due to public health interventions, vaccination, and improved sanitation. However, norovirus remains highly contagious, especially among children and the older adult. Projections suggest a continued decrease in the burden of such diseases by 2035. To further reduce this burden, preventive measures like vaccination and infection control strategies are essential for high-risk populations, alongside ongoing research into norovirus epidemiology and transmission dynamics.